(untitled) (Revista Contexto & Educação, 2022)
Society has been changed dramatically by new practices linked to the digital world, including the sphere of education and especially youth. In this context of changes, there is a pressing need to produce and update knowledge about youth identities and cultures. So, this article, the result of quantitative research, with 806 questionnaires applied to students in public high schools from the city of Uberlândia, Minas Gerais (Brazil), presents some socio-digital behaviors of these young people, permeated by biocultural, social and economic aspects, such as age, sex, ethnicity, religion, region, work and family income. Among its results, we highlight the fact that there is no univocal profile of young people from Uberlandia in public high school, but rather different profiles that depend on multiple socioeconomic factors that, in turn, influence and are influenced by their own digital culture. Our research shows that it is possible to understand, simultaneously, global youth, connected to the remote world, and a local one, from the digital uses of young brazilians, mineiros and uberlandenses who attend public schools and whose digital culture is deeply marked by the intersection of economic, spatial, religious and ethnic dimensions.